International Institutional Law : Seventh Revised Edition - Schermers, Henry G., (International Law E-Books Online, Collection 2025., 2025)
This seventh, revised edition of International Institutional Law covers the most recent developments in the field. Although public international organizations such as the United Nations, the World Trade Organization, the World Health Organization, the African Union, ASEAN, the European Union, Mercosur, NATO and OPEC have widely divergent objectives, powers, fields of activity and numbers of member states, they also have many institutional characteristics in common. There is unity within diversity. Rather than being a handbook for specific organizations, the book offers a comparative analysis of the institutional law of international organizations. It includes chapters on the rules and practices concerning membership, institutional structure, decision-making, financing, legal order, supervision and sanctions, legal status and external relations. The books theoretical framework and extensive use of examples from practice is designed to appeal to both academics and practitioners.